Problematic Loci of Synergetic Analysis of Innovative Educational Processes - Konovalchuk, Ivan (Pedagogical Discourse, 2013)
Legitimacy and expediency of the use of synergetic methodology for research of educational innovations are proved. Problematic loci of research of innovative educational processes which need the application of synergetic approach are defined and can find the decision in coordinates of synergetics. Synergetic methods allow to open new semantic aspects of processes and mechanisms of self-development and self-organization of innovative pedagogical systems. In accordance with the principles of systematic synergism innovations are characterized as being self determined, non lineal, feasible, bifurcative, multivariate in changes and the subjects of innovation are also being creative.